Merging Securely M2M Protocols, Internet of Things and Cloud Computing - Darwish, Dina (Discoveries in Agriculture and Food Sciences, 2019)
The Internet of Things provides new ways for communication through the Web world using object-enabled networks. At the same time, M2M devices intercommunication and their communication through the web if they were connected to the Internet, presents new challenges, especially in security, that traditional communication models have not yet fully solved. Because of their inborn un-watched, minimal effort and mass-sent nature, M2M devices, and remote communication architectures and solutions for these devices, would encapsulate new dangers in security. These threats are not fully faced by use of security technologies and methods implemented in existing wireless devices, cellular networks or WLANs. The use of cloud computing gives a convenient, on demand and scalable network access to a shared pool of configurable computing resources and devices. This paper concentrates on a secure method to integrate the M2M protocols with the Internet of Things (IoT) and Cloud Computing under the name of Secure Machine-to-Internet Clouding (SM2IC) architecture. The secure design for integrating M2M protocols, along with IoT and cloud computing is proposed. To apply this design, an IoT enabled smart home scenario was examined to analyze secure communication between M2M devices and IoT applications. Also, the cloud computing is used to include different cloud applications, such as, IaaS, PaaS, and SaaS for monitoring the quality of service of M2M devices through IoT applications. Then, simulations were performed to test the proposed security technique, followed by conclusions and future work.